Factors influencing chemotherapy knowledge in women with breast cancer - Parker, Pearman D. (Appl Nurs Res, 2020)
BACKGROUND: Chemotherapy knowledge is linked to managing side effects, reducing exposure to potential infection, and adjusting lifestyle behaviors while going through treatment. However, no research exists regarding the influence of patients’ personal attributes on chemotherapy knowledge. AIM: The aim of this study was to describe the relationships of health literacy and demographics on chemotherapy knowledge among women with breast cancer undergoing treatment. METHOD: We used a descriptive, exploratory design with convenience sampling of women with breast cancer receiving intravenous chemotherapy who completed one mandatory education session. Participants completed a demographic questionnaire and three instruments: 1) Rapid Estimate of Adult Literacy – Short Form (REALM-SF); 2) Shortened Test of Functional Health Literacy in Adults (S-TOFHLA); and 3) Leuven Questionnaire on Patient Knowledge of Chemotherapy (L-PaKC). We used univariate linear regression and ANOVA to identify how health literacy and demographics influenced chemotherapy knowledge. RESULTS: The REALM-SF (p = 0.022) and S-TOFHLA (p = 0.023) scores were significantly associated with chemotherapy knowledge. Chemotherapy knowledge scores were affected by marital status (p = 0.018) and income (p < 0.001) where married women had significantly higher chemotherapy knowledge scores (M = 92.6, SD = 6.6) than women who were divorced (M = 83.3, SD = 16.7) with a knowledge score difference of −9.3 between the groups (p = 0.02). Comparisons showed significant differences of chemotherapy knowledge between women with differing income levels. CONCLUSIONS: This study highlights the relevance of considering patients’ health literacy and personal attributes such as marital status and income when teaching about chemotherapy.